The flow experience in Chinese art exhibitions: developing an immersive evaluation system - Gao, Jie; Hu, Xin (Frontiers in Virtual Reality, 2025)
IntroductionIn innovative art exhibitions, we create an immersive and interactive exhibition experience, where the audience can feel the transformation between virtual and reality, giving them a relaxed and pleasant sense of immersion. For example, we can improve people’s sense of immersion through interactive design, study how to use VR virtual reality technology in art exhibitions, and design visual immersion generated by large-screen interaction. Most of the research focuses on immersive technology in art exhibitions, but for the abstract concept of immersion, it is difficult to judge the audience’s immersive experience in the exhibition. This research aims to explore the factors that affect the audience’s sense of immersion in art exhibitions based on the flow theory, and to build an evaluation system for evaluating the audience’s sense of immersion.MethodsFrom the perspective of flow experience, we conducted research on multiple immersive art exhibitions to explore the interactive relationship between the audience, exhibits, and exhibition halls. We used the unstructured observation method to conduct preliminary research and analysis, and used the Delphi method to let experts score the design indicators (10 in the first round and 25 in the second round) to obtain various design indicators for immersive exhibitions. Finally, we used the analytic hierarchy process to determine the weights of the evaluation indicators and establish an immersive evaluation system in art exhibitions.ResultsThe results show that from the perspective of flow experience, the three main aspects of evaluating immersion in art exhibitions are the impact of the exhibition’s own value, the audience’s immersive experience, and the creation of environmental immersion. Constructing these three evaluation levels can measure the audience’s demand for highquality exhibition experience.DiscussionThe evaluation system of immersive art exhibitions constructed by this research provides a basis for the effectiveness of evaluation of future immersive art exhibitions. Starting from the sense of immersion, it explores how to concretize the sense of immersion and how to judge it. It emphasizes the process of quantifying the sense of immersion of the audience in art exhibitions.